PENDIDIKAN LINGKUNGAN DALAM APLIKASI PEMBELAJARAN - Nabil Tito Prasetyo; Imam Syafei; Baharudin, Ali Murtado (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Environmental education is an important aspect in developing ecological awareness in students from an early age. This paper aims to analyze the approaches, methods, and applications of environmental education in the learning process. The approaches used include interdisciplinary, contextual, participatory, and problem- based learning, which are considered capable of fostering active student involvement in understanding environmental issues. Meanwhile, the methods used include field observations, case studies, discussions, and debates that serve to develop critical and analytical thinking skills, as well as an attitude of concern for the environment. The application of environmental education is carried out by utilizing the real environment, integration into subjects, and the use of digital technology- based media. The results of this study confirm that environmental education implemented innovatively can increase ecological awareness, build 21st-century skills, and instill values of social responsibility and desire in students.